M13 The use of online health forums by chronic cough sufferers. (15th November 2016) - Sinha, A; Wilson, AM; Porter, T
Abstract : Introduction: Chronic cough represents a significant health problem, affecting 10–20% of the population, for which effective medical support is often unavailable. 1 In such circumstances, and having exhausted medical options, patients may turn to online health forums to exchange support and seek information. 2, 3 We aimed to determine how patients use health forums and in turn, how medical professionals might utilise them in clinical practice. Methods: Three prominent open health forums were searched for threads related to cough, and screened against inclusion criteria adapted from the BTS guidance on cough 1 . Included threads were transcribed verbatim into QSR NVIVO, and subjected to qualitative thematic analysis. Findings were validated through the use of multiple reviewers. Results: 96 threads were reviewed, with contributions from 223 forum users. Three predominant themes emerged: the impact of chronic cough, treatment suggestions, and supportive posts. Regarding the impact of chronic cough, users highlighted the physical and psychological sequelae from prolonged chough, and the limitations imposed upon daily activities. Users suggested both prescribed treatments and alternative remedies, with many offering potential diagnoses to query with medical professionals. Supportive posts involved various strategies designed to show sympathy and empathy with others. Conclusions: Chronic cough patients use health forums to exchange information, advice and support. Health forums are a potential tool for clinicians wishing to access this population to provide medical care and promote patient education. We propose further research into these opportunities. References: Morice AH, McGarvey L, Pavord I. Recommendations for the management of cough in adults. Thorax 2006;61 (suppl 1):i1–i24. Nelson S, Hwang KO, Bernstam EV. Comparing clinician knowledge and online information regarding Alli (Orlistat). Int J Med Inform 2009;78 (11):772–7. Poole R, Smith D, Simpson S. How patients contribute to an online psychoeducation forum for bipolar disorder: A virtual participant observation study. JMIR Mental Health 2015;2 (3):e21.